(untitled) (International Journal of Latest Technology in Engineering Management & Applied Science, 2025)
Abstract: There are several studies on decolorization and degradation of azo dyes by ozonation. However, the combined treatment of ozonation followed by aerobic biodegradation for mixed azo dyes has not been reported much. As prolonged ozonation alone is costly so aerobic degradation which is cheaper has been studied after ozonation to make overall treatment economic. The effect of ozonation on the degradation process of mixed azo dye solution, containing four azo dyes, CI Acid Red14 (AR14), Congo Red (CR), CI Reactive Black 5(RB5), CI Reactive Violet 5(RV5) each of 250 mgl-1 has been studied in the semi batch rector. The parameters such as pH, absorbance (at maximum wavelength), conductivity, COD, TOC and BOD5 were monitored during the ozonation process at different time intervals with influent ozone dose of 55.8 g, O3m-3. The results obtained indicate that ozonation is highly effective way to remove the color of synthetic dye solutions but still lots of organic contents remain at that time. Determination of coefficients of decay for individual dyes from ozonated samples of mixed dye by high performance thin layer chromatography (HPTLC) showed that decay rates of reactive dyes as well as di-azo dyes were less compared to other dyes and mono azo dyes. BOD5 data revealed that partial oxidation of mixed azo dyes by ozonation increases the biodegradability (BOD5/COD ratio increases from .01 to 0.42) after 80 min ozonation. More then 90% reduction in COD and TOC takes place for mixed dye after 60 min ozonation followed by aerobic biodegradation. Results of integrated treatment indicate that treated wastewater may be disposed in water bodies or may be considered for reuse.